MENGELOLA KONFLIK PADA LEMBAGA PENDIDIKAN ISLAM - Yesi Ulandari; Junaidi (CV. ADIBA AISHA AMIRA, 2025)
Conflict in Islamic educational institutions is a complex issue and needs to be managed well to create a harmonious learning environment. In this context, education serves not only as a process of knowledge transfer, but also as a means of individual character building in society. Conflict can arise from a variety of sources, including disagreements over curriculum, leadership, and cultural and ideological differences among students and teachers This research aims to explore the definition of conflict and how it is managed in Islamic educational institutions. Several definitions of conflict have been put forward by management and psychology experts, suggesting that conflict can be positive or negative depending on how it is managed. The objectives of conflict management in Islamic education institutions include creating a harmonious environment, improving communication and maintaining focus on educational goals The types of conflicts that often occur in Islamic education institutions include conflicts over curriculum, leadership, between teachers and students, and financial issues. Conflict resolution can be done through the principles of deliberation, mediation, strengthening character education, and improving communication and fair leadership. With the right approach, educational institutions can manage conflicts constructively and improve the quality of education The importance of parental involvement and policy evaluation is also emphasized as a preventive measure. So In conclusion, effective conflict management not only prevents disputes but also supports better achievement of educational goals